Percepción sobre el proceso de acreditación e implementaciones desarrolladas por los docentes de la Facultad de Odontología, Universidad de Costa Rica (UCR) - Hernández Rivera, Patricia (2014)
This study assesses the perception of the faculty at the Dental School of University of Costa Rica, about the accreditation obtained in April 30, 2009, and evaluates the implementation developed as part of this improvement process. The survey evaluates the quantity of scientific publications and participations in teaching courses before and after 2009, to assess the effect caused by the accreditation on the performance of the teachers. To quantify the perceptions, faculty were asked to rate the acceptation or rejection to some statements that were used to qualify the accreditation process. The survey was completed by 81 teachers, which had at least a quarter time appointment. The results lead us to deduce that the surveyed faculty agrees with the accreditation of the School, because they accept the statements about positive aspects of the accreditation, with the approval rate ranging between 63.75 y el 87.5%. Those statements classified as negative were disapproved by most of the teachers in a range between the 47.5 y 63.7%. Concerning the implementations made by the teachers, there was an increase in the quantity of publications made after the accreditation and in the teacher training courses has been equated to the historic accumulated in two years. In conclusion this investigation permits to suggest that the faculty is committed with the accreditation and in general, actions are being implemented to successfully achieve the re-accreditation